Impact of additional cytogenetic aberrations at diagnosis on prognosis of CML: long-term observation of 1151 patients from the randomized CML Study IV - Fabarius, Alice; Leitner, Armin; Hochhaus, Andreas; Müller, Martin Christian; Hanfstein, Benjamin; Haferlach, Claudia; Göhring, Gudrun; Schlegelberger, Brigitte; Jotterand, Martine; Reiter, Andreas; Jung-Munkwitz, Susanne; Proetel, Ulrike; et al. (Blood, 2011)
The prognostic relevance of additional cytogenetic findings at diagnosis of chronic myeloid leukemia (CML) is unclear. The impact of additional cytogenetic findings at diagnosis on time to complete cytogenetic (CCR) and major molecular remission (MMR) and progression-free (PFS) and overall survival (OS) was analyzed using data from 1151 Philadelphia chromosome-positive (Ph+) CML patients randomized to the German CML Study IV. At diagnosis, 1003 of 1151 patients (87%) had standard t(9;22)(q34;q11) only, 69 patients (6.0%) had variant t(v;22), and 79 (6.9%) additional cytogenetic aberrations (ACAs). Of these, 38 patients (3.3%) lacked the Y chromosome (−Y) and 41 patients (3.6%) had ACAs except −Y; 16 of these (1.4%) were major route (second Philadelphia [Ph] chromosome, trisomy 8, isochromosome 17q, or trisomy 19) and 25 minor route (all other) ACAs. After a median observation time of 5.3 years for patients with t(9;22), t(v;22), −Y, minor- and major-route ACAs, the 5-year PFS was 90%, 81%, 88%, 96%, and 50%, and the 5-year OS was 92%, 87%, 91%, 96%, and 53%, respectively. In patients with major-route ACAs, the times to CCR and MMR were longer and PFS and OS were shorter (P < .001) than in patients with standard t(9;22). We conclude that major-route ACAs at diagnosis are associated with a negative impact on survival and signify progression to the accelerated phase and blast crisis.